Comprehensive Energy Management - Safe Adaptation, Predictive Control and Thermal Management - Watzenig, Daniel; Brandstätter, Bernhard; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The book discusses the emerging topic of comprehensive energy management in electric vehicles from the viewpoint of academia and from the industrial perspective. It provides a seamless coverage of all relevant systems and control algorithms for comprehensive energy management, their integration on a multi-core system and their reliability assurance (validation and test). Relevant European projects contributing to the evolvement of comprehensive energy management in fully electric vehicles are also included. This volume includes contributions on model based functional safety and fault-tolerant E/E architectures, advanced control making use of external information (from a cloud) as well and thermal management as a central part for energy optimization and finally some aspects on fuel cells. The second volume (ISBN .....) includes chapters on ECO driving and ECO routing covering different approaches for optimal speed profiles for a given route (mostly interconnecting withcloud data). .
Safe Adaptation for Reliable and Energy-Efficient E/E Architectures -- Model-Based Functional Safety Engineering -- Model Predictive Control of Highly Efficient Dual Mode Energy Storage Systems Including DC/DC Converter -- Predictive Energy Management on Multi-Core Systems -- Holistic Thermal Management Strategies for Electric Vehicles -- Heat Pump Air Conditioning Systems for Optimized Energy Demand of Electric Vehicles -- Thermal Management of PEM Fuel Cells in Electric Vehicles.
Keywords: Automotive engineering; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Control engineering; Automotive Engineering; Engineering Thermodynamics, Heat and Mass Transfer; Control and Systems Theory